Brazilian More Doctors Program: assessing the implementation of the Education Axis from 2013 to 2015 - Oliveira, Felipe Proenço De; Pinto, Hêider Aurélio; Figueiredo, Alexandre Medeiros De; Cyrino, Eliana Goldfarb [UNESP]; Oliveira Neto, Aristides Vitorino De; Rocha, Vinícius Ximenes Muricy Da (UNESP, 2019)
Abstract The More Doctors Program (PMM) was created in 2013. Guided by social needs, it set a new regulatory framework for medical education and residency in Brazil. This study is based on public policies and their actions aimed at implementing changes in medical education in PMM, as well as their results until 2015, by analyzing documents from official sources and the literature. The following results were identified: decrease in regional inequalities in the distribution of undergraduate course seats; education internalization; increase in medical residency seats specialized in Family and Community Medicine; expansion of preceptorship qualification; and creation of the National Registration of Specialists. The challenges faced by PMM to effectively achieve its goals, the need for State commitment and the current threats to this vital dimension of the program (ensure the right to health) are pointed out.

Resumen El Programa Más Médicos fue creado en 2013 y estableció un nuevo marco regulador para la formación y residencia médica en Brasil. En este artículo se han realizado análisis documentales, análisis de bases de datos oficiales y revisión de literatura, buscando estudiar los cambios en la formación médica y sus resultados hasta 2015. Se han identificado avances importantes en la distribución de plazas de graduación entre las diferentes regiones del país; en la interiorización de la formación; en la creación de cursos de medicina que sigan la regulación estatal; en la regulación de las plazas de residencia médica con enfoque en medicina de familia y comunidad; en la cualificación de la preceptoría; y en la creación del Catastro Nacional de Especialistas. En la conclusión se señalan los desafíos que ha enfrentado para alcanzar efectivamente sus objetivos.

Resumo O Programa Mais Médicos (PMM), criado em 2013, estabeleceu novo marco regulatório para a graduação médica e a residência médica no Brasil, tendo a necessidade social como orientadora do processo. A presente reflexão pauta as políticas públicas e suas ações direcionadas à implementação de mudanças na formação médica no PMM e seus resultados até 2015, por meio de análise documental de fontes oficiais e literatura. Identificou-se: redução nas desigualdades regionais na distribuição de vagas de graduação; interiorização da formação; expansão de vagas de residência médica com enfoque na medicina de família e comunidade; expansão da qualificação da preceptoria; e criação do Cadastro Nacional de Especialistas. São apontados desafios enfrentados pelo PMM para alcançar efetivamente seus objetivos, a necessidade de comprometimento do Estado e as atuais ameaças a essa dimensão vital do programa, que busca a garantia do direito à saúde.
Programa Más Médicos: evaluación de la implantación del Eje Formación de 2013 a 2015
Programa Mais Médicos: avaliando a implantação do Eixo Formação de 2013 a 2015
Keywords: Primary healthcare; Medical education; More Doctors Program; Public policies.; Atenção primária à saúde; Educação médica; Programa Mais Médicos; Políticas públicas.